Cytokine Storm: The Primary Determinant for the Pathophysiological Evolution of COVID-19 Deterioration - Chen, Ruirong; Lan, Zhien; Ye, Jujian; Pang, Limin; Liu, Yi; Wu, Wei; Qin, Xiaohuan; Guo, Yang; Zhang, Peidong (Frontiers in Immunology, 2021)
The coronavirus disease 2019 (COVID-19) pandemic caused by the novel severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is an ongoing major threat to global health and has posed significant challenges for the treatment of severely ill COVID-19 patients. Several studies have reported that cytokine storms are an important cause of disease deterioration and death in COVID-19 patients. Consequently, it is important to understand the specific pathophysiological processes underlying how cytokine storms promote the deterioration of COVID-19. Here, we outline the pathophysiological processes through which cytokine storms contribute to the deterioration of SARS-CoV-2 infection, and describe the interaction between SARS-CoV-2 and the immune system, as well as the pathophysiology of immune response dysfunction that leads to acute respiratory distress syndrome (ARDS), multi-organ dysfunction syndrome (MODS), and coagulation impairment. Treatments based on inhibiting cytokine storm-induced deterioration and occurrence are also described.